Given differential equation is, "p^2(x^2-a^2)-2xyp+y^2+a^4=0"
I can write it as,
"p^2x^2-2xyp+y^2=a^2p^2 - a^4"
"\\implies (y-xp)^2 = a^2(p^2-a^2)"
Then, "(y-xp) = \\sqrt{a^2(p^2-a^2)}"
"y=xp \\pm \\sqrt{a^2(p^2-a^2)}"
This equation is same as charpit's equation, "y = xf(p)+\\phi(p)"
So general solution of the equation will be,
"y=cx \\pm \\sqrt{a^2(c^2-a^2)}"
where c is any constant.
For particular solution, we need some boundary conditions.
Let x = 0 at y=0
then,
"0=0c \\pm \\sqrt{a^2(c^2-a^2)} \\implies c = \\pm a"
so, particular solution will be,
"y=\\pm ax"
Comments
Leave a comment